The Influence of Non-Physical Work Environment, Satisfaction, and Motivation on Employee Performance at PT Eurotruk Transindo Samarinda - Nela Yesika Lelang; Khairil Anwar; Tuti Wediawati; Fareis Althalets (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
The development of the business world in the digital era requires every company to adapt quickly and implement innovative strategies in order to remain competitive. PT Eurotruk Transindo Samarinda faces increasingly fierce competition due to the emergence of various new companies in various sectors, thus requiring optimal human resource management that is in line with the dynamics of digital transformation. This study aims to analyze the influence of non-physical work environment, job satisfaction, and motivation on employee performance at PT Eurotruk Transindo. This study uses a quantitative approach with data collection techniques through observation and the distribution of questionnaires to 50 respondents, which were then analyzed using statistical tests with the assistance of SPSS version 31. The results of the study indicate that non-physical work environment and work motivation have a positive and significant impact on employee performance, while job satisfaction does not have a significant impact. Simultaneously, all three variables have a significant impact on employee performance. These findings emphasize the importance of aligning human resource management strategies with business transformation to enhance employee performance and maintain competitiveness in the digital era.